Blockchain's Impact on Coffee Supply Chains: A Systematic Literature Review - Rina, Rina; Rahmayu, Mulia; Hidayat, Taopik (JURNAL TEKNIK KOMPUTER AMIK BSI, 2025)
Coffee is a globally significant commodity with high economic value and extensive social impact. Nevertheless, the intricate nature of the coffee supply chain frequently leads to issues concerning visibility, traceability, and sustainability. Blockchain offers a decentralized, transparent, and secure approach to mitigate these problems effectively. This research seeks to explore the current trends, core motivations, and auxiliary technologies that facilitate the integration of blockchain technology within the coffee supply chain. A total of 16 scientific articles published in Scopus-indexed journals (Q1 to Q4) between 2019 and 2024 were selected and analyzed using the Systematic Literature Review (SLR) method. The findings reveal that traceability and transparency are the primary focuses of blockchain implementation. The study also identifies several supporting technologies, such as smart contracts, Distributed Ledger Technology, IoT, NFT, and Artificial Intelligence, which play critical roles in enhancing the efficiency and security of blockchain-based coffee supply chains.